Tracing the origins and transformations of fluorescence dissolved organic matter within western and eastern Greenland’s shelves: a comparative study - Monika Zabłocka; Piotr Kowalczuk; Joanna Stoń-Egiert; Elena Terzić; Elena Terzić; Evanthia Bournaka; Artur P. Palacz (Frontiers in Marine Science)
Differences in the composition and spatial distribution of Fluorescent Dissolved Organic Matter (FDOM) between western and eastern Greenland shelf waters reflect the interplay of distinct regional environmental drivers-such as glacial meltwater inputs and stratification effects – which shape local DOM processing and biogeochemical cycles. These contrasts provide unique opportunity to understand how Arctic coastal system responds to climatic changes. To investigate these dynamics, we assessed FDOM by an application of multivariate statistical method - Parallel Factor Analysis (PARAFAC) on samples collected in July 2021 and August 2022. The PARAFAC enabled the distinction of five components representing both humic-like (C1 (λEx/λEm 318/392), C2 (λEx/λEm 363(261)/445), C5 (λEx/λEm 399/513)) and protein-like (C3 (tyrosine) − λEx/λEm 267/305, (C4 (tryptophan) − λEx/λEm 285/345)) substances, showing variations between western and eastern shelves and across different water layers (surface, deep chlorophyll a maximum depth – DCM, and below it (i.e., in the West Slope Greenland Core water – WSGC, and in the core Polar Water - PW). The analysis showed that western DOM is almost equally composed of humic-like (51%) and protein-like (49%) substances, while the eastern shelf is dominated by protein-like FDOM (56%), indicating a stronger influence of autochthonous production in the east. The highest fluorescence intensity was measured of the protein-like component C3 in both eastern (PW layer) and western (DCM layer) shelves. In the surface waters of the western Greenland shelf we found a statistically significant (p<0.001), although relatively weak (R = 0.27) correlation between Ip and the total chlorophyll a concentration, Tchla. Derived values of spectral indices (HIX, BIX, and FI), and a ratio of fluorescence intensities of protein-like components to fluorescence intensities of humic-like components, Ip/Ih, indicated that the FDOM in analyzed water was predominantly autochthonous, characterized with low molecular weight and low-saturation aromatic rings. This findings provide new insights into FDOM composition in the Arctic under changing climatic conditions.